Drenažni sistem zgornje nezasičene cone kraškega vodonosnika - primer zaledja izvira Hubelj - Trček, Branka (Geologija, 2004)
A drainage system and a solute transport of a karst aquifer were studied by using an indirect research method basing on natural tracers. The research of mechanisms that cause the flow and solute transport from an aquifer upper unsaturated zone was particularly stressed. This zone was observed in a catchment area of the Hubelj spring, at the experimental field site of Sinji vrh. The results provided an insight into the age structure and hydrodynamics of the karst system groundwater and produced information on the aquifer recharge, storage and discharge processes, as well as on mechanisms that affected them.
Keywords: hidrodinamika; hidrogeologija; Hubelj; kraške vode; kraški izviri; kraški vodonosniki; podzemne vode; sledenje; Slovenia; Slovenija; vodni tok